2021
DOI: 10.14260/jemds/2021/199
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of One Minute Preceptor Teaching in Improving Clinical Skills of Nursing Undergraduate Students

Abstract: BACKGROUND Nurse educator has to do clinical teaching when students are posted either in clinical or community field. Clinical teaching is a method of teaching to an individual or group of students who came in contact with patients when they are posted in clinical or in community field. Clinical education enhances appropriate link between theory and practice and at the same time provides opportunity to have a practice on how to solve complex problems of health care, provide safe care and enhance critical think… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The findings revealed that preceptors used structured learning activities as opportunities for collaboration, occasions for reflection, ways to develop new educational structures and recommendations for development. Another model is the 1‐min preceptor (OMP) teaching model (Shambharkar et al, 2021). The OMP module has been shown to be effective in improving students' clinical skills in managing minor ailments, making decisions and enhancing their critical thinking.…”
Section: Introductionmentioning
confidence: 99%
“…The findings revealed that preceptors used structured learning activities as opportunities for collaboration, occasions for reflection, ways to develop new educational structures and recommendations for development. Another model is the 1‐min preceptor (OMP) teaching model (Shambharkar et al, 2021). The OMP module has been shown to be effective in improving students' clinical skills in managing minor ailments, making decisions and enhancing their critical thinking.…”
Section: Introductionmentioning
confidence: 99%